(untitled) (Economic and Political Thought, 2018)
The article aims to examine the European federalism movements from World War II until present time with respect to evolution that took place in the field of proposed ideas, concepts and visions concerning the European federation. The elements of historical and comparative analysis made it possible to prove that the federalists’ thought creates a coherent concept of a federal solution for Europe. At the same time, this vision maintaining coherence at all the stages of developing the European integration was adapted to the changing political and economic conditions, the current state of integration and challenges that occurred in Europe. At the same time, however, it is hard to resist the feeling that in the 1940s and 1970s, a catalogue of proposals was formulated and they serve to develop detailed concepts and, as a result, new solutions are rather rarely proposed.